Circulating CD4 T Cells Elicited by Endemic Coronaviruses Display Vast Disparities in Abundance and Functional Potential Linked to Antigen Specificity and Age. (8th February 2021) - Richards, Katherine A; Glover, Maryah; Crawford, Jeremy C; Thomas, Paul G; White, Chantelle; Sant, Andrea J
Abstract: Repeated infections with endemic human coronaviruses (hCoV) are thought to reflect lack of long-lasting protective immunity. We evaluated circulating human CD4 T cells collected prior to 2020 for reactivity towards hCoV spike proteins, probing for the ability to produce interferon-γ, interleukin-2, or granzyme B. We found robust reactivity to spike-derived epitopes, comparable to influenza, but highly variable abundance and functional potential across subjects, depending on age and viral antigen specificity. To explore potential of these memory cells to be recruited in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, we examined the subjects for cross-reactive recognition of epitopes from SARS-CoV-2 nucleocapsid, membrane/envelope, and spike. Functional potential of these cross-reactive CD4 T cells was highly variable; nucleocapsid-specific CD4 T cells but not spike-reactive cells showed exceptionally high levels of granzyme production upon stimulation. These results are considered in light of recruitment of hCoV-reactive cells into responses to SARS-CoV infections or vaccinations. Abstract : Human CD4 T-cell reactivity to endemic human coronavirus and SARS-CoV-2–derived peptides were assessed by quantifying IFN-γ, IL-2, and granzyme-B production directly ex vivo, revealing striking variability in abundance and functionality that may impact responsiveness to SARS-CoV-2 infections and vaccination.